2013
DOI: 10.1016/j.cell.2013.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Neurexin-3 Alternative Splicing trans-Synaptically Controls Postsynaptic AMPA Receptor Trafficking

Abstract: Neurexins are essential presynaptic cell-adhesion molecules that are linked to schizophrenia and autism, and are subject to extensive alternative splicing. Here, we used a novel genetic approach to test the physiological significance of neurexin alternative splicing. We generated knock-in mice in which alternatively spliced sequence #4 (SS4) of neurexin-3 is constitutively included, but can be selectively excised by cre-recombination. SS4 of neurexin-3 was chosen because it is highly regulated and controls neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
358
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(383 citation statements)
references
References 59 publications
(106 reference statements)
23
358
2
Order By: Relevance
“…In support of this supposition, LRRTM4 was recently annotated as an AMPA receptor constituent in a multiepitope proteomic analysis (35). Moreover, presynaptic neurexin-3 was recently reported to control postsynaptic AMPA receptor trafficking through direct binding to LRRTM2 (36); thus, it is probable that presynaptic PTPσ also does so by behaving similarly. Directly exploring the function of PTPσ/GPCs/LRRTM4 synaptic adhesion pathways in vivo will ultimately require systematic characterization of conditional knockout mice lacking PTPσ and/or GPCs.…”
Section: Discussionmentioning
confidence: 91%
“…In support of this supposition, LRRTM4 was recently annotated as an AMPA receptor constituent in a multiepitope proteomic analysis (35). Moreover, presynaptic neurexin-3 was recently reported to control postsynaptic AMPA receptor trafficking through direct binding to LRRTM2 (36); thus, it is probable that presynaptic PTPσ also does so by behaving similarly. Directly exploring the function of PTPσ/GPCs/LRRTM4 synaptic adhesion pathways in vivo will ultimately require systematic characterization of conditional knockout mice lacking PTPσ and/or GPCs.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, research has identified several molecules, mostly ion channels and receptors, which are functionally impaired when Nrxn expression is altered. Nrxn variants have been found to affect voltage-dependent calcium channels (9,10), GABA A R (7, 37), NMDAR (44), GABA B R (36,45), nicotinergic acetylcholine receptors (69), and AMPAR (47). These ionotropic and metabotropic receptors represent "target molecules" of Nrxn that may include some physical association, but it appears unlikely that the functional link to all these requires stable protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Each neurexin can bind to a small number of postsynaptic ligands, including neuroligins, cerebellins, and LRRTMs 11,19 ; neurexin-3a binds specifically to LRRTM2. 20,21 The serum and CSF of our 5 patients contained antibodies against neurexin-3a but not LRRTM2.…”
mentioning
confidence: 87%